Sustentabilidade na cadeia de suprimento do algodão: um estudo de caso da relação entre uma empresa de calçados esportivos e produtores de algodão orgânico - Ferraz, Fernanda Pompêo de Camargo (2018)
Early 2000s marked a new era for the fashion industry, that is demanded by the impact of its value chain emphasizing the statement that companies are assessed 'not only for the economic value that they add, but also for the social and environmental value that they create or destroy' (ELKINGTON, 2004, p. 3). Cotton chain – which represents 26% of the textile sector raw materials – turns into induction target of orientated practices for a sustainable supply chain. In this context, organic cotton sector grows representatively, moved by big brands that expand collections manufactured with organic cotton. However, organic cotton represents less than 1% of the fiber global production and its adoption has been revealed as challenging for the fashion industry due to sourcing complexity. Recognizing such context, the present research aims to contribute to an organic cotton sustainable supply chain management and seeks to answer the following question: how does the relationship between the fashion industry and organic cotton family farmers producers occur? The research uses the case study methodology, involves the cotton supply chain of the footwear company (sneakers) Veja Fair Trade. Analysis is based on the sustainable supply chain management models by Seuring and Müller (2008) and Pagell and Wu (2009). The study reveals that the relationship between the fashion industry companies and its family farmers producers included new behaviours, such as the active participation of NGOs, transparency and decommodization, involving the negotiation prior to the crop, advance payments, prices above market value and rewards. At the end are presented contribution to the sector related to production conditions improvement, youth retention on the farming and to the integration of the agroecological model to the named Industry 4.0.